Metal–Organic Framework (MOF)‐Derived Electron‐Transfer Enhanced Homogeneous PdO‐Rich Co3O4 as a Highly Efficient Bifunctional Catalyst for Sodium Borohydride Hydrolysis and 4‐Nitrophenol Reduction. Issue 70 (11th November 2020) - Dou, Shasha; Zhou, Shuqing; Huang, Hexiu; Yan, Puxuan; Shoko, Elvis; Isimjan, Tayirjan Taylor; Yang, Xiulin
Abstract: Developing a bifunctional catalyst with low cost and high catalytic performance in NaBH4 hydrolysis for H2 generation and selective reduction of nitroaromatics will make a significant impact in the field of sustainable energy and water purification. Herein, a low‐loading homogeneously dispersed Pd oxide‐rich Co3 O4 polyhedral catalyst (PdO‐Co3 O4 ) with concave structure is reported by using a metal–organic framework (MOF)‐templated synthesis method. The results show that the PdO‐Co3 O4 catalyst has an exceptional turnover frequency (3325.6 molH2  min −1  molPd −1 ), low activation energy (43.2 kJ mol −1 ), and reasonable reusability in catalytic H2 generation from NaBH4 hydrolysis. Moreover, the optimized catalyst also shows excellent catalytic performance in the NaBH4 selective reduction of 4‐nitrophenol to 4‐aminiphenol with a high first‐order reaction rate of approximately 1.31 min −1 . These excellent catalytic properties are mainly ascribed to the porous concave structure, monodispersed Pd oxide, as well as the unique synergy between PdO and Co3 O4 species, which result in a large specific surface area, high conductivity, and fast solute transport and gas emissions. Abstract : NaBH4 hydrolysis for H2 generation : A homogeneously dispersed Pd oxide‐rich Co3 O4 polyhedral catalyst with concave structure has been used as a highly active catalyst for NaBH4 hydrolysis and 4‐nitrophenol reduction. The excellent catalytic performance is attributed to the unique structure and the synergy between the PdO and Co3 O4 species.